Kualitas Visual Radiograf Periapikal Konvensional Setelah Penyimpanan di Ruang Arsip Rekam Medis RSGM Universitas Jember - Swasthi Prasetyarini; Gilbert Edgar Nurandhito; Peni Pujiastuti (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Radiologic supportive examinations are still the primary choice in helping dentists establish a diagnosis and treatment plan. Radiography is the basis of diagnostic imaging in dentistry because the main focus in this field is the hard tissue of the teeth and the bone supporting the teeth. Dental radiographic examination is an examination that supports the establishment of diagnosis, making prognosis, treatment planning, and to evaluate the results of treatment that has been carried out on patients in the field of dentistry. To determine the decline in the visual quality of conventional periapical radiographs of dentistry through the indicator of the onset of brown spots after storage for 21 months in the Medical Record Archive Room of RSGM University of Jember. This study was conducted on 75 conventional periapical radiographs as samples stored in the Medical Record Archive Room of RSGM University of Jember with a temperature of 22°C-28°C using Air Conditioner for 24 hours, illuminated with 40 W lamp, and room humidity conditions of 40%-50%. The research data were analyzed using descriptive analysis. This study shows that the storage duration of conventional periapical radiographs affects the quality of the radiographs. There is a decrease in the visual quality of conventional periapical radiographs through the indicator of brown spots after 21 months of storage in the Medical Records Archive Room of RSGM University of Jember and there is a decrease in the visual quality of radiographs according to the increase in radiograph storage time.